Water debinding behaviour of water soluble Ti-MIM feedstock. (July 2015) - Chen, G.; Wen, G.; Edmonds, N.; Cao, P.
<x content-type="archive" xml:space="preserve">Abstract</x> A water soluble polyethylene glycol (PEG) based binder system was used to formulate three feedstocks containing prealloyed Ti–6Al–4V, NiTi and blended elemental Ni/Ti powders respectively. The selection of these metal powders was to investigate the effect of powder characteristics such as particle size and particle shape. Various solid loadings were investigated in these feedstocks. The water debinding behaviours were systematically studied in terms of debinding temperature, time, sample thickness, powder characteristics and solid loading. Corresponding debinding rate was calculated from the measurements using a shrinking core reaction kinetic model.